Extension Professionals: Anticipating and Solving Common Challenges in Planning and Delivering Educational Programs - Laura A. Warner; Kathryn A. Stofer (EDIS)
The work of an Extension agent demands much more than just subject knowledge. An Extension career is exciting because no two days are the same. With that comes a variety of unexpected challenges. The delivery of programs to diverse clienteles is, in itself, a skill and something that Extension agents improve over time. This article summarizes some common problems associated with delivering Extension programs and recommends solutions. This 5-page fact sheet was written by Laura A. Warner and Kathryn A. Stofer, and published by the UF Department of Agricultural Education and Communication, September 2014.